Civic education and visions of war and peace in the Spanish transition to democracy. (3rd March 2016) - Mahamud Angulo, Kira; Groves, Tamar; Milito Barone, Cecilia Cristina; Hernández Laina, Yovana
Abstract: This article explores visions of war and peace in the education system during the Spanish transition to democracy. During those years, the Spanish state was faced with the challenge of leaving its authoritarian political past behind and forging a democratic civic culture. As the concepts of war and peace are inextricably linked to those of state and citizenship, they are a useful tool with which to examine changes in civic education. A wide variety of educational sources has been explored, with particular attention to the emotional nature of the depiction of both war and peace. This study reveals two opposing styles. The official discourse demonstrated a factual treatment of war and a tendency to concentrate on international bodies and their actions, when it came to fomenting peace. The treatment of peace in the circles of teachers' local initiatives was different. First, peace was defined not only as the absence of war but also in terms of social equality and solidarity. Second, there was a conscious effort to get the students involved in opposing war, reinforced by emotionally charged messages regarding its horrors.